Case Study of an Adolescent Young Adult Patient With Multiple Sclerosis and Unpredictable Fatigue. Issue 5 (October 2016) - Newland, Pamela; Oliver, Brant J.; Smith, Judith; Hendricks-Ferguson, Verna L.
Abstract : Female adolescent young adult patients who received a diagnosis of multiple sclerosis (MS) often experience unpredictable symptoms. Ineffective control of MS-related symptoms can adversely impact the quality of life of patients affected with MS. In this case study, we describe ( a ) a female adolescent young adult with unpredictable fatigue symptoms, ( b ) the pathophysiology of MS-related fatigue, ( c ) the National MS Society–recommended practice guidelines for fatigue, ( d ) current recommendations for pharmacology management of fatigue, and ( e ) stressors of patients with MS and their family caregivers. We propose that the use of multiple symptom-control interventions has the potential to promote quality of life and decrease suffering associated with unpredictable symptoms of MS.